Humour in Professional Academic Writing - Warchał, Krystyna (Theory and Practice of Second Language Acquisition, 2019)
Professional written academic genres are not typical sites of humour, especially in their final, published forms. In this paper, I argue that academic discourse as construed today not only does not preclude humour in written research genres but – in some text segments or in response to specific communicative needs – is perfectly compatible with it. In particular, I focus on these occurrences which engage the reader and contribute to the writer-reader rapport: humorous titles, humorous comments or asides, personal stories, and literary anecdotes. I also suggest that making university ESL/EFL students aware of the fact that “serious” writing tasks do offer some room for humour may draw their attention to the human face of academic writing, that is to the interactive, dialogic, and personal aspects of written academic communication.